Balancing Data Security: A Comparative Review of Hashing and Non-Hashing Approaches in Data Storage - Kurnia Wahyu Prima (Program Studi Teknik Komputer, 2025)
Data security is a vital pillar in modern information system management, particularly in preventing unauthorized access, data breaches, and internal misuse. Among the core techniques to protect sensitive information, hashing stands out as an essential approach, transforming original data into a fixed, non-reversible format to ensure confidentiality and integrity. However, many systems still store passwords or other sensitive data in plaintext, leaving them highly vulnerable to exploitation. This study conducts a comparative experimental analysis between two system prototypes: one implementing the SHA-256 hashing algorithm and another storing data without hashing. Tests were conducted through brute-force attack simulations and direct database inspections using phpMyAdmin on a local server environment. The findings show that the non-hashing system exposed 100% of stored passwords in readable form, allowing immediate access and manipulation by internal actors. In contrast, the hashing-based system successfully obscured password content, making it computationally infeasible to reverse even with administrative database access. These results affirm the crucial role of hashing in enhancing data protection. Beyond technical validation, this study underscores the urgency of adopting hashing as a minimum security standard in any system managing confidential data. The results highlight that incorporating cryptographic hashing not only defends against external attacks but also mitigates insider threats. Therefore, organizations and developers must treat hashing as a non-negotiable part of system architecture to ensure long-term data security, compliance with global standards, and the preservation of user trust in the digital era.